Sosialisasi Prilaku Hidup Bersih dan Sehat (PHBS) Pada Tatanan Rumah Tangga Di Desa Bonto Tiro Kecamatan Rumbia Kabupaten Jeneponto - Muawanah, Muawanah; Hasmah; A.M. Fadhil Hayat; Dewi Arisanti (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2024)
Clean and healthy living behavior (PHBS) is an important component in health development which requires awareness, ability, and the desire to live healthily from every resident so that optimal health can be achieved. Actions to maintain cleanliness to achieve optimal health can start with yourself and your family in everyday life. PHBS in the household setting is an effort to empower each household member to know, want and be able to independently be actively involved in implementing clean and healthy living behavior through the PHBS program to improve health status. The problem faced is the low level of public knowledge regarding the benefits of clean and healthy living behavior for society in general and especially for the people of Bonto Tiro village, Rumbia District, Jeneponto Regency. Therefore, the aim of community service is to provide knowledge and understanding about PHBS in the household setting. This service activity is carried out by providing education to the community through the lecture method. The extension material is displayed in powerpoint form with delivery that is easy for the public to understand. The results of this service activity were an increase in community knowledge after providing outreach about the importance of implementing clean and healthy living behavior in household settings in everyday life.